In-Silico and In-Vivo Evaluation of Luteolin and Imeglimin as Novel Therapeutic Agents in Reserpine-Induced Parkinsons Disease in Rats: Neuroprotective effects of luteolin and Imeglimin in reserpine-induced Parkinsons disease in rats - Nade, Vandana; Ahire, Vaishnavi; Kawale, Laxman; Siraskar, Balasaheb (Iranian Journal of Pharmaceutical Sciences, 2026)
Parkinson's disease (PD) is the second most prevalent late-life movement disorder, characterized as a hypokinetic condition involving selective and extensive loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc) of the striatum. This study investigated the neuroprotective effects of luteolin and imeglimin against reserpine-induced PD in rats, focusing on the dopamine transporter protein (DAT), α-synuclein aggregation, and proinflammatory cytokines using both in silico and in vivo approaches. In- silico molecular docking studies were followed by in vivo experiments. PD was induced in rats by administration of reserpine (1 mg/kg, s.c.) every other day for 3 days. Pretreatment with luteolin (50 mg/kg, p.o.) and imeglimin (100 mg/kg, p.o.) was given for 5 days. Behavioral assessments (orofacial dyskinesia, catalepsy, and rotarod) were performed on day 5, followed by biochemical and histopathological evaluations. Parameters measured included oxidative stress markers (CAT, GSH, SOD, and LPO), neurotransmitters (dopamine and nitric oxide), proinflammatory cytokines (TNF-α and IL-1β), and α-synuclein expression. Reserpine-treated rats exhibited increased catalepsy duration, orofacial dyskinesia (tongue protrusions, vacuous chewing), and impaired motor coordination. Biochemical analysis showed reduced antioxidant levels (CAT, GSH, SOD), reduced dopamine levels, and elevated LPO, TNF-α, IL-1β, and α-synuclein. Combined treatment with luteolin and imeglimin significantly mitigated these behavioral and biochemical alterations—improving locomotor activity, reducing dyskinesia, and normalizing antioxidant and inflammatory markers. Dopamine levels were restored, and α-synuclein aggregation was notably reduced. Histopathology confirmed dopaminergic neuronal preservation and reduced Lewy body formation in the treatment group. These findings suggested that luteolin and imeglimin, particularly in combination, offer neuroprotective effects in PD by reducing oxidative stress, inflammation, and α-synuclein aggregation, thereby preserving dopaminergic neurons and brain function.